Guardians of Privacy: Unraveling the Tapestry of Personal Data Protection in Indonesia and France - Ariani, Merizqa; Amboro, FL. Yudhi Priyo; Nurlaily, Nurlaily (Legal Spirit, 2024)
The rapid advancement of technology has facilitated easier access to information but has concurrently heightened the risks associated with the security of personal data. This has raised concerns about individual privacy, prompting the enactment of regulations for the protection of personal data. Legal enforcement becomes crucial to ensure proper treatment of personal data. Indonesia responded to the increasing cases of data breaches by enacting the Personal Data Protection Act in 2022. However, incidents of data leaks persist. France boasts a well-established data protection law, notably the General Data Protection Regulation (GDPR), which provides comprehensive guidelines for the management of personal data. There are similarities and differences in the approaches of the two countries. Both emphasize principles such as fairness, transparency, and responsibility. However, France highlights openness and integrity, while Indonesia places a greater focus on fairness and responsibility. Individual rights take center stage in both regulatory frameworks, with an emphasis on access, correction, and deletion of data. France introduces the rights to protest and data portability to afford individuals greater control over their personal data. Sanctions and legal enforcement are also crucial in safeguarding personal data. Both countries impose sanctions, though there are variations in implementation and enforcement. This research aims to provide a better understanding of the differences and similarities in the frameworks for personal data protection between Indonesia and France, with the goal of strengthening data protection and enhancing public awareness.